Implementation of Problem based Learning to Improve Students’ Mathematical Understanding Ability and Mathematical Connection Ability on Vocational School - Komariah, Euis Nur; Nurdin, Irfan Taufik; Putra, Harry Dwi; Yuliani, Anik ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
In achieving educational goals, mathematical understanding and connection ability are very important for students. However, the fact is mathematical understanding and connection ability still very low. So, to achieve these learning objectives, a learning approach model is needed to improve students’ mathematical understanding and connection ability. The purpose of this study is to see the improvement of mathematical understanding and connection ability on vocational shool. In order to do so, we used quasi-experimental research by comparing groups with different treatments. One class as experimental using problem based learning model and another class as control using directed learning. We used mathematical understanding and connection ability test to collect the data. The results shows that mathematical understanding and connection ability improved by using problem based learning model. N-Gain for mathematical understanding ability is in high category and mathematical connection ability is in moderate category. Based on the results, we can conclude that problem based learning model can improve mathematical understanding ability and mathematical connection ability.